Cardiometabolic Index is associated with heart failure: a cross-sectional study based on NHANES - Zhu, Xiao-Ming; Xu, Yan; Zhang, Jie (Frontiers in Medicine, 2024)
Heart failure is a complex syndrome characterized by impaired cardiac function, resulting in insufficient cardiac output to meet metabolic demands. Despite improvements in treatment, the prevalence of heart failure continues to rise, driven by aging populations and increased risk factors. The Cardiometabolic Index (CMI), a novel measure combining abdominal obesity and lipid levels, has emerged as a potential predictor of cardiac metabolic risk. This study utilized data from the NHANES database, analyzing 22,586 participants to investigate the association between CMI and heart failure. Results revealed a significant positive correlwation: as CMI increased, so did the risk of heart failure, with odds ratios of 2.77 and 1.87 for the highest quartile after adjusting for confounders. Subgroup analyses indicated heightened risks among older adults and those with hypertension or diabetes. ROC curve analysis demonstrated that CMI offers good diagnostic efficacy for heart failure, surpassing traditional measures like BMI. Our findings suggest that CMI is a valuable tool for assessing heart failure risk, highlighting the importance of addressing cardiac metabolic health in prevention and treatment strategies. Further research is needed to explore causal relationships and refine predictive models incorporating CMI.